Prevention of the spread of SARS COV-2 by Rapid Antigenic Tests on the passengers entering an Italian seaport - Savini, S.; Monaco, D.; Turci, C.; Ursino, S.; Matera, C.; Marchini, R.; Di Giovanni, T.; Ciambella, E.; Iannucci, V.; Quintavalle, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
The differences of the epidemiology (incidence, case-to-death rate, mortality, etc) of COVID-19 between USA and Italy are analyzed taking into account the social, economic and sanitary characteristics of the two countries, both severely hit be the pandemic; and the causes of the so many different behaviors of the disease in each of them are discussed and explained.